Epistemic Semantics in Guarded String Models - Eric H Campbell; Mats Rooth (Society for Computation in Linguistics, 2021)
Constructive and computable multi-agent epistemic possible worlds models are interpreted as sets of guarded string models in an epistemic extension of Kleene Algebra with Tests (KAT}). The account is framed as a formal language EpiKAT (Epistemic KAT) for defining such models. The language is implemented by translation into the finite state calculus, and alternatively by modeling propositions as lazy lists in Haskell. The syntax-semantics interface for a fragment of English is defined by a categorial grammar.
Keywords: Epistemic Semantics; Intensional Semantics; Kleene Algebra